TRAF3IP2 (TRAF3 Interacting Protein 2) Mediates Obesity-Associated Vascular Insulin Resistance and Dysfunction in Male Mice. Issue 4 (October 2020) - Grunewald, Zachary I.; Ramirez-Perez, Francisco I.; Woodford, Makenzie L.; Morales-Quinones, Mariana; Mejia, Salvador; Manrique-Acevedo, Camila; Siebenlist, Ulrich; Martinez-Lemus, Luis A.; Chandrasekar, Bysani; Padilla, Jaume
Abstract : Insulin resistance in the vasculature is a characteristic feature of obesity and contributes to the pathogenesis of vascular dysfunction and disease. However, the molecular mechanisms underlying obesity-associated vascular insulin resistance and dysfunction remain poorly understood. We hypothesized that TRAF3IP2 (TRAF3 interacting protein 2), a proinflammatory adaptor molecule known to activate pathological stress pathways and implicated in cardiovascular diseases, plays a causal role in obesity-associated vascular insulin resistance and dysfunction. We tested this hypothesis by employing genetic-manipulation in endothelial cells in vitro, in isolated arteries ex vivo, and diet-induced obesity in a mouse model of TRAF3IP2 ablation in vivo. We show that ectopic expression of TRAF3IP2 blunts insulin signaling in endothelial cells and diminishes endothelium-dependent vasorelaxation in isolated aortic rings. Further, 16 weeks of high fat/high sucrose feeding impaired glucose tolerance, aortic insulin-induced vasorelaxation, and hindlimb postocclusive reactive hyperemia, while increasing blood pressure and arterial stiffness in wild-type male mice. Notably, TRAF3IP2 ablation protected mice from such high fat/high sucrose feeding-induced metabolic and vascular defects. Interestingly, wild-type female mice expressed markedly reduced levels of TRAF3IP2 mRNA independent of diet and were protected against high fat/high sucrose diet-induced vascular dysfunction. These data indicate that TRAF3IP2 plays a causal role in vascular insulin resistance and dysfunction. Specifically, the present findings highlight a sexual dimorphic role of TRAF3IP2 in vascular control and identify it as a promising therapeutic target in vasculometabolic derangements associated with obesity, particularly in males. Abstract : Supplemental Digital Content is available in the text.